Evolution of a Linear Urban Structure - The Street-Road Type in the Porto Region. - Casas-Valle, Daniel (Lit, 2020)
Despite the actual discourse of promoting sustainable mobility, existing road networks provide often excellent accessibility conditions for mainly (individual) motorized transport, which, in many urban regions, is still dominant in the overall transport performances. This paper focuses on the transformation adaptability of the road network in the Porto region. How did the network evolve? How spatial and road planning tools were used to transform the road network? And what kind of relation exits between these tools?
Keywords: Regionalplanung; Verkehrsplanung; Regionalverkehr; Verkehrsnetz; Straßennetzgestaltung; Transformation; Landstraße; Stadtstraße; Nachhaltige Mobilität; Siedlungsstrukturentwicklung; Urbanisierung